Advanced Computing in Electron Microscopy - Kirkland, Earl J. (Springer US, 2010)
Advanced Computing in Electron Microscopy, 2nd Edition, brings together diverse information on image simulation. An invaluable resource, this book provides information on various methods for numerical computation of high resolution conventional and scanning transmission electron microscope images. This text will serve as a great tool for students at the advanced undergraduate or graduate level, as well as experienced researchers in the field. This enhanced second edition includes: -descriptions of new developments in the field -updated references -additional material on aberration corrected instruments and confocal electron microscopy -expanded and improved examples and sections to provide stronger clarity